2019
DOI: 10.1248/cpb.c19-00272
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis and Biological Evaluation of Destruxins

Abstract: The combinatorial synthesis and biological evaluation of destruxins are described herein. First, the total synthesis of destruxin E was achieved, and its absolute configuration was successfully determined to be (S). In addition, the preparation of a combinatorial library based on the structure of destruxins was carried out by the split-and-pool method. Biological evaluation of the resulting analogs against osteoclast-like multinuclear cells (OCLs) revealed that the N-methyl-alanine residue was crucial to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Therefore, this obvious herbicidal difference between 6 and 4 indicated that the Cl atom in HMPA 1 residue, maybe other halogen atoms, could significantly improve their herbicidal activities. To date, more than 35 destruxin cyclodepsipeptides had been found from various fungi cultures. , Among these destruxins, destruxin E series had always attracted researchers’ attention because of their significant V-ATPase inhibitory activities and great potential in the application of cancer therapy. , The remarkable herbicidal potential of destuxin E series of 4 and 5 , which was never found before, could expand their application potential to be lead compounds for the further herbicide development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this obvious herbicidal difference between 6 and 4 indicated that the Cl atom in HMPA 1 residue, maybe other halogen atoms, could significantly improve their herbicidal activities. To date, more than 35 destruxin cyclodepsipeptides had been found from various fungi cultures. , Among these destruxins, destruxin E series had always attracted researchers’ attention because of their significant V-ATPase inhibitory activities and great potential in the application of cancer therapy. , The remarkable herbicidal potential of destuxin E series of 4 and 5 , which was never found before, could expand their application potential to be lead compounds for the further herbicide development.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Among these destruxins, destruxin E series had always attracted researchers' attention because of their significant V-ATPase inhibitory activities and great potential in the application of cancer therapy. 32,33 The remarkable herbicidal potential of destuxin E series of 4 and 5, which was never found before, could expand their application potential to be lead compounds for the further herbicide development.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The uniqueness of the endophytic fungal community is considered a promising source of novel bioactive compounds. , Destruxins (Dtxs) are a group of cyclic hexadepsipeptides that are biosynthesized by NRPS synthetase dtx s. , Dtxs were originally isolated from the entomopathogenic fungus Metarhizium anisopliae, and 35 Dtxs have been reported from the fungi. , These cyclic hexadepsipeptides are mycotoxins and can protect host plants by exerting potent insecticidal activity. Some of the derivatives have also shown neurotoxic, antifeedant, cardiotonic, and immunosuppressive effects. Dtx A has insecticidal activity by inducing the upregulation of heat shock proteins (HSPs) and damages the innate immunity of insects . Dtxs A, B, and E exhibited potent cytotoxic and antiangiogenic activities against human cancer cell lines, interfering with intrinsic apoptosis via the MAPK and PI3K/Akt pathways …”
mentioning
confidence: 99%